Implementasi Kegiatan Pentas Seni dalam Mengembangkan Minat dan Bakat Murid di SD Negeri 6 Selong - Baiq Abidaturrosida; Arif Rahman Hakim; Faizah; Silvi Diah Ayu Nurkumalahadi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to describe the implementation of performing arts activities and introduce them to develop talents and foster student interest at Selong 6 Public Elementary School. The study used a qualitative approach with a descriptive approach. Subjects included the principal, teachers, and students, selected purposively. Data were collected through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana model, which includes data condensation, data presentation, and conclusions. The results indicate that performing arts activities are held routinely every Wednesday, featuring student representatives from each class. This activity provides students with the opportunity to showcase their talents and interests. In addition to developing talent and fostering interest, performing arts also enhances self-confidence, creativity, communication skills, and cooperation among students. Challenges faced include a lack of self-confidece among some students and limited supporting facilities. The school’s efforts include providing motivation, mentoring, ongoing practice, and optimizing the use of available facilities. Thus, performing arts activities are an effective school program in supporting the optimal development of student potential.